The Effects of Lecturers’ Formal and Informal Talks on Students’ Understanding of the Material in the Language Learning Process - Dewi Purwati (Institut Agama Islam Negeri Palopo, 2020)
AbstractThis research focused on investigating the effects of lecturers’ formal and informal talks on students’ understanding of the material. The aim of this research is to elaborate how the lecturer’s talk in terms of its formal and informality could affect the students’ understanding of the material delivered in the classroom. The researcher applied qualitative method to fulfil the aim and collected the data of the research by using three instruments which were classroom observations, recording of the teaching and learning process, and interview of the students. All teaching processes and interviews were recorded and transcribed and analysed using discourse analysis approach. The data was analyzed by adopting the six facets of understanding proposed by Wiggins & McTighe (2018). The research was conducted at the first and fifth semester groups of English Study Program of IAIN Bone. The result shows that the lecturers used both formal and informal language alternately in teaching. The students preferred the lecturer to use informal language in delivering the material. According to them, using informal language made the students easier to understand the material delivered by the lecturer. They argued that teaching method and including the variation of lecturer’s language in teaching gave a significant improvement to the students’ achievement and understanding. The students fulfilled all the six facets of understanding based on the theory Wiggins & McTighe (2018). It meant that the students had a complete understanding of the material delivered by the lecturers.